Social and economic dimensions of water resources - silva hernández, francisca; martínez prats, German; silva hernández, Francisca; Martínez prats, German; silva hernández, francisca; martínez prats, German (Corporación Universitaria Americana, 2021)
Introduction: water is a natural resource, which today being a vital limited liquid turns out to be of national and global security interest, raising a conflict of interest in its reserve, use, management and distribution. Objective: to describe an overview of the social and economic dimensions of water resources based on their use. Materials and Methods: it is structured based on a qualitative methodology of documentary type, from the consultation of books, scientific articles in virtual databases, reports, internal and international normative instruments that allowed to develop a descriptive and interpretative scope of the water resource. Results: the added value to a natural resource such as water, has created transformation and adaptation to processes of its use, management, reserve, scarcity, maintenance and distribution, in which, the interest or vision regarding water has shaped the social and economic systems of the various societies. Conclusions: the dimensions presented give a panorama in various categories of water as a limited vital liquid that puts societies in a situation of water stress, in a state of vulnerability of the right to life individually and collectively, transgressing the state of sustainable well-being in which the various sectors of society are to ensure access and guarantee of the minimum liquid vital.